2021
DOI: 10.1136/bmjpo-2020-001013
|View full text |Cite
|
Sign up to set email alerts
|

Large decrease in paediatric hospitalisations during the COVID-19 outbreak in Japan

Abstract: We evaluated the nationwide trends in paediatric hospitalisations including non-emergency hospitalisations during the COVID-19 pandemic in Japan. Using inpatient data from 272 acute-care hospitals covering 12.4% of total hospitalisations of all ages, we analysed the number of hospitalisations of children (aged 1–17 years) for weeks 9–21 of 2020 (during the outbreak) versus 2017–2019. Hospitalisation decreased during the outbreak by 38.4% (adjusted incidence rate ratio, 0.60; 95% CI, 0.53 to 0.69). There were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…The MDV database has been widely used in previous studies. 22 , 23 , 24 , 25 The age distribution of inpatients in the MDV database is roughly similar to that of all DPC hospitals, whereas the hospital volume (i.e., the number of beds) tends to be larger (Supplementary Table 1). Laboratory test values were available for approximately 10% of participating hospitals that agreed to provide the data.…”
Section: Methodsmentioning
confidence: 88%
“…The MDV database has been widely used in previous studies. 22 , 23 , 24 , 25 The age distribution of inpatients in the MDV database is roughly similar to that of all DPC hospitals, whereas the hospital volume (i.e., the number of beds) tends to be larger (Supplementary Table 1). Laboratory test values were available for approximately 10% of participating hospitals that agreed to provide the data.…”
Section: Methodsmentioning
confidence: 88%
“…This was in line with other studies reporting similar reductions in children with high triage urgency or need for hospital admission. [6,[30][31][32][33][34][35][36][37][38] Defining the harm of delayed presentations, as well as establishing what contributed to a possible delay, can be difficult. [39] In an attempt to distinguish the delay in seeking care from harm sustained, Roland et al concluded that only a minority (6 out of 51 (11.8%))…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have published results showing an increased proportion of complicated cases in the COVID-era [ 2 – 4 , 8 – 10 ]. However, some studies have found only reductions of uncomplicated cases [ 5 , 11 – 16 ] or no change [ 17 ]. Several of these latter studies are registration studies having the advantage of having more data from more centres.…”
Section: Discussionmentioning
confidence: 99%